Law in the system of social regulation - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2024)
People’s activities are carried out within the framework of established social structures. Each type of social norms has its own regulatory capabilities. Among them, law has a priority role, since law is entrusted with the mission of ensuring the self-preservation of society. The issue of developing a generally accepted definition of law continues to remain relevant. Various concepts of legal understanding are proposed. The starting point for understanding law is idealistic or materialistic ideas about it. The right of an abstract subject is enshrined in legislation. In the process of law enforcement activities, other social regulators are also involved in legal relations, and as a result of such symbiosis, the individual right of the subject is formed.
Keywords: law; social norms; state; subject; individual law